Aplikasi Re-Used Katalis Pada Sintesis Emulsifier - Ricfan Anggriawan; Ida Zahrina; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Mono and diglycerides (MDAG) are a group of synthetic emulsifiers usually used for food emulsion. MDAG can be obtained by the esterification process of fatty acids and glycerol with Deep Eutectic Solvents (DES) as a catalyst. The re-used catalyst method is one of many methods to determine the effectiveness of DES as a catalyst in the esterification process. DES is a mixture of at least two components, there are Hydrogen Bond Acceptors (HBA) and Hydrogen Bond Donors (HBD) which form eutectic phases with a melting point is lower than the constituent component. Re-used catalyst DES was tested in optimum condition with temperature 150°C, 30 minutes reaction time, 5 wt% catalyst, with 6:1 ratio mol between glycerol and oleic acid, and the conversion is 95%. The result of 5 times re-used catalyst is the conversion has got a not too significant reduction, which indicates that the phosphonium-based DES catalyst has a strong resistance to maintaining high catalyst activity in the esterification process. Keywords: esterification, catalyst, DES, Emulsifier, re-used catalyst.